Efficacy of Probiotics for Irritable Bowel Syndrome: A Systematic Review and Network Meta-Analysis - Zhang, Tao; Zhang, Cunzheng; Zhang, Jindong; Sun, Feng; Duan, Liping (Frontiers in Cellular and Infection Microbiology, 2022)
Background Irritable bowel syndrome (IBS) is a common gastrointestinal condition. Studies regarding the treatment of IBS with probiotics have not yielded consistent results, and the best probiotics has not yet been confirmed. Therefore, we performed a network meta-analysis (NMA) to assess the relative rank order of different probiotics for IBS. Method We searched for RCTs on the efficacy of probiotics for IBS until August 25, 2021. The primary outcome was the symptom relief rate, as well as global symptoms, abdominal pain, bloating, and straining scores. The NMA was conducted using Stata 15.0. We also used meta-regression to explore whether the treatment length and dose influenced the efficacy. Results Forty-three RCTs, with 5,531 IBS patients, were included in this analysis. Firstly, we compared the efficacy of different probiotic species. B.coagulans exhibited the highest probability to be the optimal probiotic specie in improving IBS symptom relief rate, as well as global symptom, abdominal pain, bloating, and straining scores. In regard to the secondary outcomes, L.plantarum ranked first in ameliorating the QOL of IBS patients, but without any significant differences compared with other probiotic species in standardized mean differences (SMD) estimates. Moreover, patients received L.acidophilus had lowest incidence of adverse events. The meta-regression revealed that no significant differences were found between participants using different doses of probiotics in all outcomes, while the treatment length, as a confounder, can significantly influence the efficacy of probiotics in ameliorating abdominal pain (Coef = -2.30; p = 0.035) and straining (Coef = -3.15; p = 0.020) in IBS patients. Thus, we performed the subgroup analysis on treatment length subsequently in these two outcomes, which showed that efficacy of B.coagulans using 8 weeks ranked first both in improving the abdominal pain and straining scores. Additionally, B. coagulans still had significant efficacy compared to different types of probiotic combinations in present study. Conclusions The findings of this NMA suggested that B.coagulans had prominent efficacy in treating IBS patients, and incorporating B.coagulans into a probiotic combination, or genetically engineering it to amplify its biological function may be a future research target to treat IBS patients. With few direct comparisons available between individual therapies today, this NMA may have utility in forming treatment guideline for IBS with probiotics.